Futebol feminino em perspectiva histórica: o machismo estrutural e a deslegitimação de Marta como rainha do futebol - Oliveira, Amanda Coelho Cruz Alves de (Universidade Federal de São Carlos, 2026)
This study aims to analyze manifestations of hate speech directed at women’s football, especially toward the athlete Marta Silva, observing how these statements resume historically constructed meanings about the place assigned to women in sports. The research is based on the symbolic contradiction between the consecration of a “King of football” and the difficulty in legitimizing a “Queen of football”, focusing on comments about the athlete Marta Silva on social media. As a theoretical foundation, the concepts of statement and archive by Michel Foucault, the discussions on structural sexism by Pierre Bourdieu, and the concept of technodiscourse by Marie-Anne Paveau are used. The analysis demonstrates that many comments reproduce misogynistic discourses and reinforce historical inequalities still present in women’s football.
Women's football in historical perspective: structural sexism and the delegitimization of Marta as queen of football
Keywords: Futebol feminino; Discurso de ódio; Machismo estrutural; Análise do discurso; Women’s football; Hate speech; Structural sexism; Discourse analysis; LINGUISTICA, LETRAS E ARTES::ARTES; 5. Igualdade de Gênero; 10. Redução das Desigualdades; 16. Paz, Justiça e Instituições Eficazes